PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK MAKE-A MATCH DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP NEGERI 5 SOLOK - Putri, Mella Winny; Rismen, Sefna; Mardiyah, Ainil (STKIP PGRI Sumbar, 2013)
This research from concept comprehension mathematically students that still low, they less active, their motivation in learning math is still low. This research has goal to know wheter comprehension mathematically concept students which including comprehension learning at grade VII SMP Negeri 5 Solok. This experiment research with research design Random Toward Subject. The population of this research is students grade VII SMP Negeri 5 Solok Academic Year 2012-2013 that conclude in seven classes. To decide this experiment class and control class doing by random, selected class VIIF as a experiment class and class VIIE as a control class. The instrument that using in this research is comprehension math concept test. The result of data analysis known both of the class get normal distribute and homogenius is Î± = 0,05 and the result hypothesis test with MINITAB getting p-value = 0,001, so the hypothesis in this research is accepted. So, in conclusion the math concept students comprehension that applied model of Cooperative Learning by techniques Make-A Match better than the math concept students comprehension in convensional learning at student grade VII SMP Negeri 5 Solok academic year 2012-2013 with credibility level 95%.